Src controls tumorigenesis via JNK‐dependent regulation of the Hippo pathway in Drosophila. (30th November 2012) - Enomoto, Masato; Igaki, Tatsushi
Abstract : Cell–cell interactions within the tumour microenvironment have crucial roles in epithelial tumorigenesis. Using Drosophila genetics, we show that the oncoprotein Src controls tumour microenvironment by Jun N‐terminal kinase (JNK)‐dependent regulation of the Hippo pathway. Clones of cells with elevated Src expression activate the Rac‐Diaphanous and Ras‐mitogen‐activated protein kinase (MAPK) pathways, which cooperatively induce F‐actin accumulation, thereby leading to activation of the Hippo pathway effector Yorkie (Yki). Simultaneously, Src activates the JNK pathway, which antagonizes the autonomous Yki activity and causes propagation of Yki activity to neighbouring cells, resulting in the overgrowth of surrounding tissue. Our data provide a mechanism to explain how oncogenic mutations regulate tumour microenvironment through cell–cell communication. Src controls tumorigenesis via JNK‐dependent regulation of the Hippo pathway in Drosophila : This report shows that oncoprotein Src activates Yki via inactivation of the Hippo pathway and simultaneous activation of JNK, which antagonizes Yki cell‐autonomously causing propagation of Yki activity to neighbouring cells and inducing overgrowth of surrounding tissue.